Peptide Composition of Skin Extracts Depending on Its Physiological State - Salienko, I. A.; Bogatyreva, O. O.; Galchenko, S. E.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2008)
The effect of traumas of different types and injection of skin extracts of newborn piglets or pig’s spleen on peptide composition of aqueous-saline extracts of rat’s skin. It has been established that peptide composition of skin extracts depends on trauma type. Injection of piglets’ skin extract or pigs’ spleen in abdominal cavity of rats changes the peptide composition of normal skin extract, promotes regenerative of cold traumas and normalization of molecular-mass spectrum of the substances of peptide origin in extracts of traumatized skin.